Irene Pomeroy papers - Pomeroy, Irene
Three letters (1845) from Nauvoo, Ill., and one letter (1854) from Great Salt Lake City, Utah, describing Mormon pioneer life.
Mormon pioneer.
Collection material in English.
Forms part of: Miscellaneous Manuscript collection.
Keywords: Mormons -- Illinois -- Nauvoo -- History -- 19th century; Mormons -- Utah -- Salt Lake City -- History -- 19th century; Women pioneers -- Illinois; Women pioneers -- Utah